К "последнему" морю: ист. роман / В. Г. Ян ; авт. предисл. И. Греков ; худож. И. Кусков - Ян Василий Григорьевич (Правда, 1984)
Экземпляры: ф.11 (20181024) / Инвентарный номер: 89113 / Цена: 1.40 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Я 60 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6